Images, beliefs and truth at the 2013 and 2015 protests - França, Vera Veiga; Bernardes, Mayra (RuMoRes, 2016)
This article links two remarkable occurrings in Brazil’s contemporary history: the 2013’s “jornadas de junho” and the 2015’s pro-impeachment protests. Through the concepts of front, truth and violence, we organize an analytic route in three stages: a look over the “jornadas de junho”, a perusal at the 2015’s protests through photographs and a reflection on the implications and unfoldings of 2013 found in 2015’s protests.